Use of essential oils in active food packaging: recent advances and future trends - Ribeiro-Santos, R. (2021)
Background: Essential oils (EOs) extracted from plants have been the focus of numerous researches due to their potential in the food and pharmaceutical industries and aromatherapy. Scope and approach: The effectiveness of EO may be observed in antimicrobial and antioxidant tests. Volatile compounds are present in EOs and are responsible by their biological activities, namely antimicrobial and antioxidant capacity. Several manuscripts and patents have emerged with applications of EOs and their constituents, and their incorporation into food packaging. These packages with EOs have shown efficiency against microorganisms and oxidants in vitro, in tests with food and/or food simulants evaluation tests. In line with this, chromatographic techniques can be used to identify the main volatile compounds present in EOs or to determine the compounds that migrated from packaging to food or food simulants. This review provides a concise and critical insight in the use of EOs with emphasis in food applications. The innovative food packaging applications are highlighted and future trends are discussed. Key findings and conclusions: In general, EOs extend food stability during storage, inhibiting the growth of spoilage or pathogenic microorganisms and protecting against oxidation. Moreover, in spite of the potential of EOs, more studies should evaluate their safety and possible side effects before considering their use for food purposes.